A bibliometric analysis of global trends in the research field of pharmaceutical care over the past 20 years - Wang, Yu; Rao, Yifei; Yin, Yuling; Li, Yaolei; Lin, Zhijian; Zhang, Bing (Frontiers in Public Health, 2022)
Pharmaceutical care is essential in building up the basics of public health and clinical care. A comprehensive understanding of global status in the field of pharmaceutical care is necessary for directing its research frontiers and future trends. Therefore, this study aims to make a bibliometric analysis to track the development of pharmaceutical care research worldwide during the past two decades. The publications regarding pharmaceutical care were culled from the Web of Science Core Collection (WoSCC). Countries, institutions, authors, journals, references, and keywords in this field were visually analyzed by using VOSviewer (version1.6.17) and CiteSpace (Version 5.8.R3). As a result, 3597 publications (3177 articles and 420 reviews) were obtained. The annual yields grew more than three times in the past two decades, from 54 records in 2002 to 379 papers in 2021. The United States played the leading role in this research from multiple aspects, including publication (n=1208), citations (n=28759), funding agencies, and collaboration worldwide. The University of Sydney in Australia was the most contributed institution with the greatest number of publications (n=112) in pharmaceutical care research. Hersberger KE from the University of Basel was the most productive author (n=40). Chen TF from the University of Sydney was the author who owed the highest H-index of 19 and most citations (n=1501). They both significantly impacted this field. American Journal of Health System Pharmacy produced the most publications, while Pharmacotherapy had the highest IF (IF2020=4.705) in this field. Clusters networks of co-cited references and keywords suggested that clinical pharmacy is an essential theme in pharmaceutical care. Terms of medication safety and critical care recognized by burst analysis of keywords also hint at the recent attention on clinical pharmacy. The present bibliometrics analysis may provide a comprehensive overview and valuable reference for future researchers and practitioners in the research field of pharmaceutical care.